Over The Limit of Authority of The Constitutional Court In Resolving Disputes About The Results of The General Election - Sodikin Sodikin (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
The limits of authority possessed by the Constitutional Court in deciding disputes regarding the results of general elections as stipulated in Article 24C paragraph (1) of the 1945 Constitution have given a narrow interpretation which is to assess the difference in the figures set by the KPU. The limited authority of the Constitutional Court has caused the decline in the quality of elections. The Constitutional Court does not dare to take on its broader authority even though its position as guardian of the constitution as well as the guardian of democracy. The wider authority of the Constitutional Court needs to be given that every election will always be followed by violations and fraud.